Efeitos psicossociais da otoplastia em crianças com orelhas proeminentes (em abano) - Gasques, José Alvaro Lourenço (2004)
Objective: To appraise the psychosocial effects of otoplasty on children suffering from prominent ears. Casuistic and Method: A total of 15 male and 15 female patients were studied, with ages ranging from 6 to 14 years, clinical diagnosis of prominent ears and complaints related to the presence of this deformity. Pre-operative social competence and behavioral disturbance tests were applied to the children s guardians and teachers. Additionally, the inventory of anxiety trait-state for the child (Idate C) and the child depression inventory (CDI) were employed, as was a self-image study using drawings. Six months after corrective otoplasty by the Converse technique used by Tanzer, all the children were re-assessed. The statistical analysis was performed for pure scores in the descriptive phase using basic statistics, the mean, standard deviation, median and percentages. To compare the pre- and post-operative phases, the non-matched indication test of the median was used. Results: When the CBCL was applied to guardians, there were reductions in the anxiety and depression, aggressiveness and attention, thinking and social deficits. There were also improvements in both school and out-of-school activities. When the CBCL was applied to the teachers, reductions in anxiety and depression, aggressiveness, attention and social deficits, somatic complications and impulsiveness were observed. Improvements in academic performance, stable work, learning and happiness were also evidenced. Comparing the anxiety state assessed in the pre- and post-operative periods using Idate C, we observed that 18 had a reduction in anxiety in the post-operative period, 2 remained the same and 7 children had an increase. Comparing the anxiety traits of the children, we verified that in 8 the anxiety diminished, 14 had no changes and in 5 the anxiety trait increased in the post-operative period. Analysis using CDI demonstrated that all patients with moderate pre-operative depression suffered from mild depression after the surgery. In relation to the drawings in the pre- and post-operative periods, we noted that a new somatic image was formed, creating a new sensorial perception of the internal world and a better adaptation to the self and to others (relations, environments). The surgical technique used for the correction of protruding ears, otoplasty, is recognized and employed in several specialist services giving harmonious and satisfactory anatomical results in the post-operative period of all patients.